Ginkgolic Acid is a Multi-Target Inhibitor of Key Enzymes in Pro-Inflammatory Lipid Mediator Biosynthesis - Gerstmeier, Jana; Seegers, Julia; Witt, Finja; Waltenberger, Birgit; Temml, Veronika; Rollinger, Judith M.; Stuppner, Hermann; Koeberle, Andreas; Schuster, Daniela; Werz, Oliver (Frontiers in Pharmacology, 2019)
Introduction: Lipid mediators (LMs) comprise bioactive metabolites of polyunsaturated fatty acids, including pro-inflammatory prostaglandins (PGs), thromboxanes (TXs), and leukotrienes (LTs), as well as specialized pro-resolving mediators (SPMs). They are essentially biosynthesized via cyclooxygenase (COX) and lipoxygenase (LO) pathways in complex networks and regulate the progression as well as the resolution of inflammatory disorders including inflammation-triggered cancer. Ginkgolic acid (GA) is a phenolic acid contained in Ginkgo biloba L. with neuroprotective, antimicrobial, and antitumoral properties. Although LMs regulate microbial infections and tumor progression, whether GA affects LM biosynthesis is unknown and was investigated here in detail. Methods: Pharmacophore-based virtual screening was performed along with docking simulations. Activity assays were conducted for isolated human recombinant 5-LO, cytosolic phospholipase (PLA)2α, COX-2, and ovine COX-1. The activity of human mPGES-1 and thromboxane A2 synthase (TXAS) was determined in crude cellular fractions. Cellular LM formation was studied using human monocytes, neutrophils, platelets, and M1- and M2-like macrophages. LMs were identified after (ultra)high-performance liquid chromatography by UV detection or ESI-tandem mass spectrometry. Results: GA was identified as virtual hit in an mPGES-1 pharmacophore-based virtual screening. Cell-free assays revealed potent suppression of mPGES-1 activity (IC50 = 0.7 µM) that is fully reversible and essentially independent of the substrate concentration. Moreover, cell-free assays revealed COX-1 and TXAS as additional targets of GA with lower affinity (IC50 = 8.1 and 5.2 µM). Notably, 5-LO, the key enzyme in LT biosynthesis, was potently inhibited by GA (IC50 = 0.2 µM) in a reversible and substrate-independent manner. Docking simulations support the molecular interaction of GA with mPGES-1 and 5-LO and suggest concrete binding sites. Interestingly, interference of GA with mPGES-1, COX-1, TXAS, and 5-LO was evident also in intact cells with IC50 values of 2.1–3.8 µM; no radical scavenging or cytotoxic properties were obvious. Analysis of LM profiles from bacteria-stimulated human M1- and M2-like macrophages confirmed the multi-target features of GA and revealed LM redirection towards the formation of 12-/15-LO products including SPM. Conclusions: We reveal GA as potent multi-target inhibitor of key enzymes in the biosynthesis of pro-inflammatory LMs that contribute to the complex pharmacological and toxicological properties of GA.